Total iron absorbed from iron-biofortified potatoes is higher than from non-biofortified potatoes: a randomized trial using stable iron isotopes in women from the Peruvian highlands - Burgos, G.; Liria, R.; Zeder, C.; Kroon, P.A.; Hareau, G.; Penny, M.; Dainty, J.; Al-Jaibaji, O.; Boy, Erick; Mithen, R.; Hurrell, R.F.; Salas, E.; et al. (Elsevier, 2023)
Background Yellow fleshed potatoes biofortified with iron have been developed through conventional breeding but the bioavailability of the iron is unknown.